Computational analysis of machining characteristics of surface using varying concentration of nanofluids (Al2O3, CuO and TiO2) with MQL. (2021) - Tiwari, Anamika; Agarwal, Deepak; Singh, Anurag
Abstract: When the Nanoparticles are mixed at different concentration in Basefluid, are called Nanofluid. By the addition of different nanoparticles at different concentration in different basefluid we get the enhancement of different-different properties which we are going to analyze in this paper. In this article, we are going to analyze the nanoparticles (Al2 O3, CuO and TiO2 ) at concentration (0%, 1%, 2%, 3%, 4%, 5% and 6%) into the basefluid (water) through MATLAB and obtain the different input parameters like Thermal Conductivity; Specific Heat; Viscosity; Density and we get that during different parameter analysis different nanofluids shows their property enhancement hence we can we different nanoparticles during different machining process according to the properties we required for machining. After that we do a theoretical study that how these input parameters affect the output parameters like Surface Roughness, Machining Temperature, Chip Morphology, Tool Wear, Coefficient of Friction, etc. during the machining or metal removal process. The summary and conclusions are also presented on basis of data collected and some area for future research is also identified.